Exploring the survival & livelihood strategies used by retail sector workers in Johannesburg against the backdrop of low remuneration - Mukorombindo, Zivai Sunungukayi (My University, 2015)
Retail sector workers have been identified as some of the lowly paid labourers in South Africa and the world at large. This research was aimed at gaining a comprehensive understanding of the livelihood of retail industry workers who are on low remuneration in the city of Johannesburg, a city which demands a lot financially. The study was also targeted at exploring the survival strategies that are being used by the workers in the midst of their low wage woes i.e. how they are managing to survive on a very low pay. The research attempted to understand the nature and dynamics of the strategies that may be used as well as the experiences of the workers in relation to this. The study adopted a qualitative research approach as it sought to gain personal experiences of the workers. Therefore in-depth interviews were used to collect data from 15 workers employed in the retail sector in Johannesburg who were selected using purposive and snowball sampling. The findings of the study confirmed that retail sector workers’ remuneration is too low to such an extent that they can be classified as the working poor since they struggle to afford even the basic necessities in life. There are a number of strategies that are used by the workers to survive under low remunerations and these include making alterations in livelihood like turning to accommodation and arrangements which are affordable. However the biggest strategy which proved to be pivotal for the survival of the workers is social capital and social networks. Other income generating proved to be unpopular with the workers because they require time which the workers do not have, but the argument presented in this research is that with high unemployment rate in the country and lack of post-matric education, it leaves the workers without a lot of options in terms of greener pastures. Therefore low paid workers need to be innovative and adopt entrepreneurship ideas to substantiate their inadequate salaries. This is also essential in that the capital class in South Africa has been given a lot of power therefore it is not easy for the workers to bargain for a better wage therefore as strides are being made on an organisational level to negotiate for better pay, workers in the meantime should turn to other means of augmenting their income.
A research report submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements of the Degree of Master of Arts in Development Sociology.